376 The prevalence, circumstances and reporting of patient/visitor-on-worker (type ii) violence in 6 U. S. hospitals. (11th October 2013) - Pompeii, L P; Schoenfisch,; Dement,; Jones,; Hester,; Smith,
Abstract : Objectives: We aimed to establish baseline measures of type II violence (patient/visitor-on-worker) and event reporting practices among workers in 6 U. S. hospitals. Findings from this survey will inform the development and implementation of a hospital violence surveillance system. Methods: An anonymous cross-sectional survey was administered to workers to examine their career and 12-month prevalence of being victims of workplace violence perpetrated by patients and/or visitors, as well as details about events that workers deemed the most serious. Results: Of the 5, 312 hospital workers who responded, 49.4% and 38.9% reported a career and 12-month prevalence of type II violence, respectively. The total number of events in the prior 12 months included 1, 100 physical assaults, 2, 206 physical threats, and 5, 676 verbal abuse events. More than half of the events were reported by nursing staff (36.7%) and patient care technologists (14.8%). Other workgroups not typically considered to be at risk also reported events including those in pharmacy, social work, food service, housekeeping, and patient financial services. Of the 2, 098 most serious events in the prior year, perpetrators were more likely to be patients (76.1%) than visitors (23.9%). Factors that workers attributed to these events included patients' behavioural issues, being disoriented, being drunk, and visitors being unhappy with patient's care and long wait-times. A large proportion (75.0%) of workers indicated they reported the event; however, only a small proportion of those (26.2%) did so through a formal system (e.g., first report of injury), while most reported verbally (58.9%) to coworkers/managers or documented in the patient's chart (14.9%). Conclusion: While the prevalence and number of violent events was high, the reporting of events by workers into a formal system was low. Reporting systems developed specifically for capturing type II violent events are needed for purposes of informing and evaluating targeted workplace violence prevention strategies.